Paham Radikalisme Berdasarkan Perspektif Agama (Radicalism Based On Religious Perspective) - Rohman, Syaiful; Nurhasanah, Siti (UI Scholars Hub, 2019)
Radicalism has become a threat in the diversity of nation and state, this is caused by a lack of tolerance toward diversity that has become a natural tendency. Radicalism has become a threat in the diversity of nation and state, this is caused by a lack of tolerance toward diversity that has become a natural tendency. This radicalism originated from an understanding about religion, which gave rise to a fanatical attitude which assumed that their religion is the only true religion in the word. Manhaj tajfiri's belief about mankind which recently has been found in the society has actualy existed since the fourth caliphate. In the history and its development called khawarij. Khawarij can be eradicated, however the thought evolved in various firqah. Right now it has been found many extreme, textual, and fundamental thoughts. This radicalism group is very incentive to instill its paradigms so that not a few young people are sedated by that paradigm. This research is conducted to find ways to prevent the spread of radical understanding. This research applies descriptive analytic method by analyzing the existing data and sources. The result of this research in form of recommendations for the government and religious leaders who should be vigorous in embedding humanist and moderate Islamic values at the grassroots level, such as adding religious and moral lessons in Islamic Educational Centers such as TPA (Al- Qur'an educational centers), Madrasas, and Islamic Boarding Schools. The effort to cultivate Islamic humanist values from an early age will be realized if there are synergies between various parties such as the government, religious leaders, and religious institutions.